Frequency of SARS-CoV-2 Infection after Vaccination in Health Care Workers in Ardabil, 2021 - Bahari, Yeganeh; Abootalebidariasari, Ghasem; Aghabalaii, Moharam; Mohammadzadeh Shahla, Mahdi (Advances in Nursing & Midwifery, 2024)
Abstract Introduction: The effectiveness and safety of COVID-19 vaccines have been reported, but there is limited information on their real-world effectiveness and reports of breakthrough infections. This study aimed to determine the frequency of COVID-19 infections after vaccination among medical interns and personnel in Ardabil city in 2021. Methods: This cross-sectional descriptive study included 330 medical interns and personnel from Ardabil city hospitals. Participants were required to provide consent, have received at least one dose of the COVID-19 vaccine, and not have hearing or speech problems. Data was collected using a researcher-made questionnaire and analyzed using SPSS software. Results: Most of the individuals involved (59.7%) were aged between 20 and 30, and 58.5% were women. The majority of the participants were married (60.6%), while physicians and nurses were the most frequently observed professional groups (with 39.7% and 29.1% respectively). Sinopharm and AstraZeneca vaccines were the most commonly used (39.4% and 17.9%, respectively). The majority of participants (67.3%) received three doses of the vaccine, and 27.1% of participants (92 people) reported getting sick at least 2 months after receiving the COVID-19 vaccine. There was no significant association between demographic variables and post-vaccine infection. Conclusions: Although a substantial number of participants were infected with COVID-19 following vaccination, the severity of the illness was mostly mild, demonstrating the value of vaccination in lessening the impact of COVID-19.